Dynamics of vortex evolution in a 2D baffled tank. (January 2016) - Wu, Chih-Hua; Faltinsen, Odd Magnus; Chen, Bang-Fuh
Abstract: A finite difference method with coordinate transformation and fictitious cell approach were used to analyze the vortex generation and shedding phenomenon for sloshing liquid in 2D tanks with baffles. The detailed description of the dynamics of vortex evolution for sloshing fluid in a tank with baffles is seldom seen in the literatures and is firstly reported in this study. The exploration of liquid sloshing in a 2D tank with vertically bottom-mounted baffles is demonstrated. The benchmark tests of a tuned liquid damper (TLD) solved by the present numerical scheme show good agreements with the reported results. The experimental measurement is also carried out in this study and the present numerical simulation has excellent accuracy according to the comparison between the computational results and experimental measurement. The evolution of vortices inside a baffled tank in terms of vortex generation, vortex shedding and the trajectories of vortices are analyzed. Four phases of interaction processes of vortices are categorized in this work. The comprehensive discussions include the evolution of vortices and vortex shedding around the baffle tip, the vortex size generated in the vicinity of the baffle tip, the shedding frequency of the vortices, and the interaction of vortices inside the tank with various heights of the baffles and liquid depths. The vortex shedding phenomenon in the vicinity of the baffle tip is tightly correlated with the strength of the vertical jet along the baffle walls and the excitation frequency of the tank. Vortex size is closely correlated with the baffle height. When the baffle height is small ( d b ≤ 0.2 d 0 ), the vortex size mainly grows in the horizontal direction. Instead, the vortex size dominantly develops in the vertical direction as d b ≥ 0.3 d 0 . The period of the generation and shedding of vortices near the baffle tip is nearly about one half of the excitation period of the tank. The dynamics of vortex evolution is closely related to the growth and the hydrodynamic interaction of the vortices and sensitively depends on the baffle height, liquid depth, excitation frequency, and excitation displacement of the tank.